Application of dry powders of six plant species, as soil amendments, for controlling Fusarium solani and Meloidogyne incognita on pea in pots - Abd-El-Khair, Hassan (2023)
The dry powder of pomegranate peel (as the rate of 10 g/1 kg soil)highly reduced the Fusarium- disease assessments (pre-emergence and post-emergence damping-off and root-rot diseases incidence), followed by spearmint leaves, caraway seeds, fennel seeds, garlic gloves and onion bulbs, respectively. The tested dry powder of plant species showed the nematicidal activity on M. incognita criteria, i.e. second juvenile (J2) in soil and roots as well as galls and egg-masses in roots of pea. The spearmint leaves, onion bulbs and fennel seeds highly reduced the J2 in soil and roots as well as galls and egg-masses. The pea plant growth parameters i.e. length of shoot, fresh & dry weights of shoot and fresh weight of roots, yield parameters, i.e. fresh and dry weight of pea pod and pod parameters as well as Rhizobium nodules number were increased in pea plants with reducing infestation with F. solani and M. incognita.